First Report of bacterial wilt disease of banana caused by Klebsiella variicola in Malaysia - Toh, Wai Keat (Plant disease, 2024)
In Malaysia, bananas (Musa spp.) are the second most cultivated fruit and the fourth most cultivated fruit in terms of export revenue. In October 2018, about 5.0 out of 6.6 hectares of a banana plantation located in Teluk Intan, Malaysia, was impacted by an outbreak of banana disease. The onset of bacterial wilt symptoms is characterized by initial leaf wilting, followed by the subsequent withering of the entire plant during later stages, fruit stalk and fruit pulp discoloration, fruit rotting, and pseudostem necrosis. The diseased banana's symptomatic pseudostems and fruit pulps were surface-sterilised in 70% ethanol for 30 s, followed by 2% NaClO for 3 min, rinsed three times in sterilised water, and cut into small pieces approximately 5 mm2 in size. The tissues were macerated in a sterilised 0.85% NaCl solution for 5 min, and the resulting suspension was streaked onto nutrient agar, followed by incubation at 28°C for 2 days. After incubation, bacterial colonies with five unique morphological characteristics were observed. Two colonies of each unique morphological type were randomly chosen and subjected to preliminary bacterial identification by 16S rRNA gene sequencing. Based on BLASTn analysis, the five unique morphological types of bacteria were preliminarily identified as Enterobacter cloacae, Citrobacter farmeri, Klebsiella variicola, Kosakonia radicincitans, and Phytobacter ursingii. Previous reports identified K. variicola and K. radicincitans as banana pathogens, but Malaysia has yet to report the former. The amplified partial 16S rDNA sequences of both K. variicola isolates (designated as UTAR-BC1 and UTAR-BC2; GenBank accession numbers: PP531448 and PP531460, respectively), which were chosen to be the focus of this study, exhibited complete similarity to each other and were 100% identical (1426/1426 identity and 1420/1420 identity, respectively) to K. variicola (CP026013.1). To verify the identity of the bacterial isolate, three housekeeping genes, namely, infB(PP538994), rpoB (PP538995), and gyrB (PP538996) of UTAR-BC1, were amplified, sequenced, and subjected to multilocus phylogenetic analysis via the neighbour-joining method (1,000 bootstrap values). Phylogenetic analysis revealed that UTAR-BC1 belongs to the K. variicola clade. A pathogenicity assay of UTAR-BC1 was conducted on 4-month-old healthy banana plantlets (cv. Nangka) using the pseudostem injection method (Tripathi et al., 2008). First, UTAR-BC1 was grown overnight in nutrient broth and then adjusted to 108 CFU/ml in a sterile 10 mM MgCl2 solution. A total volume of 100 µL of the bacterial suspension was injected into the pseudostem of five healthy banana plantlets via a syringe with a needle. Control plants were mock-inoculated with a sterile 10 mM MgCl2 solution. The experiments were replicated thrice and inoculated plants were maintained at room temperature with natural sunlight and humidity, which resembled the field conditions. Two months after inoculation, all of the UTAR-BC1 inoculated spots of banana plantlets showed severe necrosis, while the banana leaves showed symptoms of wilted appearance, whereas the control plants remained symptomless. The reisolated pathogen from 90% of the symptomatic pseudostems and leaf blades shares the same morphological and molecular features as UTAR-BC1, thus fulfilling Koch's postulates. Previously, K. variicola has been reported to be a banana pathogen causing rhizome rot in India (Loganathan et al., 2021), plantain soft rot in Haiti (Fulton et al. 2020), and sheath rot and bulb rot in China (Sun et al., 2023; Jiang et al., 2024). To the best of our knowledge, this is the first report of bacterial wilt disease in bananas attributed to K. variicola in Malaysia. This finding will facilitate the surveillance of K. variicola as an emerging pathogen in banana plants in this region, thereby safeguarding the country's food security and promoting socio-economic growth